Relative efficacy of agricultural spray oil and azadirachtin against two-spotted spider mite (Tetranychus urticae) on cucumber (Cucumis sativus) under greenhouse and laboratory conditions - DEKA, SIKHA; TANWAR, R K; SUMITHA, R; SABIR, NAVED; BAMBAWALE, O M; SINGH, BALRAJ (The Indian Journal of Agricultural Sciences, 2011)
Laboratory and greenhouse experiments were conducted on relative efficacy of agricultural spray oil and azadirachtin for the management of two-spotted spider mite (Tetranychus urticae on cucumber (Cucumis sativus L.). The treatments included the spray of agricultural spray oil, azadirachtin and combination of both at 0.1, 0.5, 1 and 2% under laboratory conditions and 0.1 and 0.5% under greenhouse conditions, replicated thrice. The laboratory experiment results indicated highest mortality of the mite after 24, 48 and 72 hr of spray in agricultural spray oil + azadirachtin (at 1 and 2%), followed by 2% agricultural spray oil alone in both the seasons. Greenhouse experiment results also indicated highest mortality of the mite on spraying agricultural spray oil + azadirachtin (0.5%) throughout the period, however, agricultural spray oil (0.5%) resulted in highest mortality only a day after spraying during the first season.